Dairy Business Analysis Project: 2007 Financial Summary - Albert De Vries; Russell Giesy; Mary Sowerby; Lane Ely (EDIS)
AN213, a 19-page illustrated report by A. De Vries, R. Giesy, M. Sowerby, and L. Ely, summarizes the financial performance of 21 dairy farms that participated in a 2007 survey. It is intended for general use by dairy farmers, the allied industry, government, and educational professionals. Published by the UF Department of Animal Science, March 2009.